A high performance proton exchange membrane fuel cell catalyst material and method of making same
Patent Information
- Application Number
- CN202610206598.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-02-12
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2046-02-12
AI Technical Summary
[0005]为了克服现有技术的上述缺陷,本发明的实施例提供一种高性能质子交换膜燃料电池催化剂材料及其制备方法,解决了传统燃料电池催化剂活性低、稳定性差、成本高、制备工艺复杂的问题
1、该发明,抗坏血酸作为还原剂,在95℃的水热条件下将氧化石墨烯片上的含氧官能团部分还原,使得石墨烯还原成共轭sp2碳结构,从而提升导电性,石墨烯之间形成π-π共轭作用和疏水作用增强,同时部分未完全还原的含氧基团可作为物理交联点,在这些驱动下石墨烯片相互搭接、缠绕、自发组装成连续孔道的三维网络结构。
Smart Images

Figure CN122068057B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of catalytic materials technology, and specifically to a high-performance proton exchange membrane fuel cell catalyst material and its preparation method. Background Technology
[0002] Proton exchange membrane fuel cells (PEMFCs) have shown broad application prospects in new energy vehicles, portable power supplies, and distributed power generation due to their high energy conversion efficiency, fast start-up, and environmental friendliness. However, the slow kinetics of the oxygen reduction reaction (ORR) at the cathode severely restrict the overall performance of the fuel cell. Therefore, the development of high-performance catalysts has become crucial to overcoming this technological bottleneck. Currently, commercial catalysts generally employ carbon-supported platinum (Pt / C) materials, utilizing the high catalytic activity of platinum to promote ORR. However, traditional Pt / C catalysts still face a series of prominent problems in practical applications: on the one hand, platinum nanoparticles are prone to migration, aggregation, and Ostwald ripening on the carbon support surface, leading to a decrease in electrochemical active area and insufficient catalytic activity and long-term stability; on the other hand, the carbon support is susceptible to corrosion in the strong acid and high-potential operating environment of fuel cells, accelerating platinum particle detachment and deactivation, severely affecting battery life.
[0003] Furthermore, the scarcity and high cost of platinum resources are another core obstacle restricting the large-scale commercialization of PEMFCs. Reducing the amount of platinum used while maintaining or even improving its catalytic performance is an important direction in current catalyst research and development. Existing research has focused on preparing platinum-based alloys to adjust the electronic structure of platinum, thereby improving its intrinsic activity and reducing the amount of platinum required. However, traditional alloying methods often require high-temperature treatment, which easily leads to sintering and growth of metal particles and makes it difficult to achieve an ordered structure at the atomic scale, thus limiting further improvements in catalyst performance. At the same time, the complex multi-step synthesis process and harsh preparation conditions also increase the production cost and quality control difficulty of the catalyst.
[0004] In summary, developing a novel PEMFC catalyst that combines high activity, high stability, low platinum loading, and feasible preparation process is of great significance for promoting the development and commercialization of fuel cell technology. Current technologies have not yet effectively addressed the contradictions between activity, stability, cost, and process complexity, necessitating innovation in material design and synthetic methodologies to construct novel composite catalytic systems. Summary of the Invention
[0005] To overcome the above-mentioned defects of the prior art, embodiments of the present invention provide a high-performance proton exchange membrane fuel cell catalyst material and its preparation method, which solves the problems of low activity, poor stability, high cost and complex preparation process of traditional fuel cell catalysts.
[0006] To achieve the above objectives, the present invention provides the following technical solution: A high-performance proton exchange membrane fuel cell catalyst material is specifically composed of a three-dimensional graphene framework, cobalt-nitrogen-carbon microcages, and ordered Pt3Co alloy nanoparticles. Preferably, the three-dimensional graphene framework is a continuous porous three-dimensional network structure formed by hydrothermal reduction self-assembly.
[0007] Preferably, the cobalt-nitrogen-carbon microcage has a porous carbon cage structure with Co-N x Active sites are embedded in Co nanoparticles.
[0008] Preferably, the ordered Pt3Co alloy nanoparticles are ordered intermetallic compounds.
[0009] Preferably, the cobalt-nitrogen-carbon microcage is tightly embedded in the nodes of the three-dimensional graphene network, and the ordered Pt3Co alloy nanoparticles are distributed in the pores of the cobalt-nitrogen-carbon microcage.
[0010] A method for preparing a high-performance proton exchange membrane fuel cell catalyst material includes the following steps: S1: Take 100 parts by volume of graphene oxide dispersion with a concentration of 2 mg / mL into a polytetrafluoroethylene inner vessel, then add 0.5 parts by weight of ascorbic acid as a reducing agent and stir magnetically for 30 minutes to mix it evenly. Place the inner vessel into the reaction vessel and heat it to 70~100℃ and keep it at that temperature for 6~12 hours. Finally, cool it to room temperature and wash the gel with deionized water. S2: Add 100 volumes of cobalt nitrate aqueous solution to the gel prepared in S1, then let it stand for 12 hours to adsorb, and finally rinse the surface with deionized water to remove excess salt solution after adsorption. S3: Take 50 volume parts of 0.8 mol / L 2-methylimidazolium methanol solution and add it to the gel prepared in S2. Then let it stand at room temperature of 25°C for 6 hours. After the reaction is completed, wash the gel with methanol. S4: The gel prepared in S3 was freeze-dried for 24 hours, then the gel was ground into powder, and then the powder was placed in a tube furnace under an argon atmosphere and heated stepwise to obtain a three-dimensional graphene / cobalt nitrogen carbon microcage composite carrier. S5: Weigh 60 volume parts of the prepared chloroplatinic acid ethanol solution with a concentration of 5 mg / mL, then weigh 0.2 weight parts of the three-dimensional graphene / cobalt nitrogen carbon microcage composite carrier obtained in S4, add the chloroplatinic acid ethanol solution dropwise and stir into the three-dimensional graphene / cobalt nitrogen carbon microcage composite carrier, then age it at 25°C for 6 hours, and finally dry it in a 60°C oven for 12 hours to obtain the precursor. S6: Anhydrous LiCl and KCl were uniformly ball-milled into powder. Then, the precursor powder prepared in S5 was ball-milled with the mixed powder of LiCl and KCl for 30 minutes. The ball-milled powder was then placed in a tube furnace under a 10% H2 / Ar mixed atmosphere and heated to 500℃ at a rate of 5℃ / min and held at that temperature for 3 hours. After the product cooled to room temperature, it was washed with 80℃ hot water until no chloride ions were detected. Then, it was kept in 1M nitric acid at 90℃ for 2 hours and washed clean with deionized water. Finally, the product was dried in an 80℃ vacuum oven for 12 hours to obtain Pt3Co / G@CoNC. S7: Weigh 80 mg of Pt3Co / G@CoNC prepared in S6, then add 5 mL of deionized water, 12 mL of isopropanol and 20 mg of ionomer D79. Disperse the mixture ultrasonically in an ice-water bath for 1 hour to obtain a cathode catalyst slurry. Spray the cathode catalyst slurry onto one side of a 5 cm × 5 cm proton exchange membrane, controlling the cathode platinum loading at 0.15–0.20 mg Pt / cm². 2 The anode slurry uses a Pt / C catalyst with a Pt / C ratio of 20% and is sprayed onto the other side of the proton exchange membrane to control the platinum loading of the anode at 0.05~0.10 mg Pt / cm³. 2 Finally, after the coating is completed, the film is dried at 60°C for 2 hours, and the frame and diffusion layer are attached to form the film electrode. S8: Assemble the prepared membrane electrode into a single cell, then connect it to the gas pipeline and circuit, control the cell temperature to 80℃, relative humidity to 100%, and back pressure to 150kPa (abs), and perform constant current activation by passing gas to obtain the voltage under different current densities; and perform 30,000 accelerated durability tests by alternately applying a square wave voltage of 0.6V and 0.95V every 3 seconds.
[0011] Preferably, the concentration of the cobalt nitrate aqueous solution in S2 is 0.05~0.15 mol / L.
[0012] Preferably, in step S4, the ground powder is placed in a tube furnace under an argon atmosphere and heated to 350°C at a heating rate of 2°C / min and held for 1 hour, and then heated to 900°C at a heating rate of 5°C / min and held for 2 hours.
[0013] Preferably, the mass ratio of LiCl to KCl in S6 is 25~50:50~75.
[0014] Preferably, in S7, the platinum loading of the cathode is controlled at 0.15~0.20 mg Pt / cm³. 2 The platinum loading of the proton exchange membrane anode is 0.05~0.10 mg Pt / cm³. 2 .
[0015] The technical effects and advantages of this invention regarding a high-performance proton exchange membrane fuel cell catalyst material and its preparation method are as follows: 1. In this invention, ascorbic acid is used as a reducing agent to partially reduce the oxygen-containing functional groups on graphene oxide sheets under hydrothermal conditions at 95°C, thereby reducing graphene to conjugated sp2+. 2 The carbon structure enhances conductivity, and the π-π conjugation and hydrophobicity between graphene sheets are strengthened. At the same time, some incompletely reduced oxygen-containing groups can serve as physical cross-linking points. Driven by these factors, graphene sheets overlap, entwine, and spontaneously assemble into a three-dimensional network structure with continuous channels.
[0016] 2. In this invention, the remaining unreduced oxygen-containing functional groups, carboxyl and hydroxyl, contain oxygen atoms with lone pairs of electrons that react with Co in the cobalt nitrate aqueous solution. 2+ Coordination occurs, causing Co 2+ It adsorbs onto the graphene framework, forming a three-dimensional framework containing Co.
[0017] 3. In this invention, when a three-dimensional framework containing Co is immersed in a 2-methylimidazole solution, the organic ligands in the solution rapidly diffuse to Co. 2+ Nearby, Co 2+ It undergoes a coordination reaction with 2-methylimidazole molecules, each Co 2+ With the center connected to multiple ligands, ZIF-67 crystals are directly nucleated and grown on the surface and in the pores of the graphene framework. The ZIF-67 crystals formed are physically mixed with strong chemical bonds through in-situ growth on the graphene framework.
[0018] 4. In this invention, ZIF-67 begins to decompose at 350℃, while maintaining its basic morphology, Co... 2+ It will be partially reduced and coordinate with the N in the imidazole ring to form Co-N. x The active site precursor is then pyrolyzed at 900°C to form a nitrogen-rich carbon framework, and the ZIF-67 polyhedron is transformed into a porous Co-N nanoparticle-rich Co-N structure. x The carbon cage at the site, and the high temperature of 900℃ will cause some carbon atoms to rearrange to form a local graphitization structure, thereby improving the electronic conductivity and chemical stability of the carrier. The obtained three-dimensional graphene / cobalt nitrogen carbon microcage composite carrier has both a highly conductive graphene framework and a cobalt nitrogen carbon microcage with a high specific surface area and abundant active sites.
[0019] 5. In this invention, the three-dimensional graphene / cobalt nitrogen carbon microcage composite carrier draws chloroplatinic acid into the micropores by stirring and relying on capillary force. Since the chloroplatinic acid solution is limited, no liquid film will be formed on the carrier surface to ensure that Pt is uniformly distributed in the carrier pores.
[0020] 6. In this invention, the added LiCl-KCl eutectic salt melts at temperatures above 350°C to form an ionic liquid medium. This medium fully wets and encapsulates the precursor powder. Furthermore, Li and K ions form weak interactions with Pt / Co, reducing the diffusion barrier of metal atoms. Simultaneously, Pt and Co atoms are easily rearranged within the confined space, and under thermodynamic drive, they more readily form ordered intermetallic compounds Pt3Co. The physical confinement of the micropores effectively inhibits particle migration and Ostwald ripening at high temperatures, thereby controlling the size of the final alloy nanoparticles. The addition of LiCl and KCl enables the synthesis of atomically ordered Pt3Co intermetallic compounds at relatively low temperatures, while simultaneously utilizing the confinement effect of the support to control particle size, thus solving the problem of high-temperature agglomeration in the preparation of ordered alloy catalysts.
[0021] 7. This invention provides a high-speed channel for continuous and efficient electron conduction through a three-dimensional graphene framework, significantly reducing charge transfer resistance. Mesoscopically, the cobalt-nitrogen-carbon microcages embedded in the three-dimensional graphene framework have a porous structure that greatly increases the specific surface area, providing channels for oxygen adsorption, diffusion, and absorption. Simultaneously, they physically confine the internally loaded alloy nanoparticles, thus enhancing the atomic-scale Co-N microcage framework. x The active sites and the ordered Pt3Co alloy nanoparticles within the pores generate electronic interactions, which significantly enhance the intrinsic activity of redox reactions.
[0022] 8. This invention utilizes a LiCl-KCl eutectic salt system, where the molten salt acts as an ionic liquid medium at relatively low temperatures, through which LiCl... + / K + The weak interaction with the Pt / Co precursor significantly reduces the diffusion barrier of Pt and Co atoms, promoting thermodynamic rearrangement towards an ordered structure. At the same time, the synergistic confinement effect of molten salt and cobalt-nitrogen-carbon microcages restricts the migration space of metal atoms, effectively inhibiting particle growth and agglomeration at high temperatures.
[0023] 9. In this invention, the catalytic activity of Pt is closely related to the electronic structure of its surface atoms, especially the d-band center. The relatively high density of the neutral phase in the d-band of pure Pt leads to excessive adsorption capacity of O and -OH in the oxygen reduction reaction, which is not conducive to the desorption of products. When Pt combines with low electronegativity Co, electrons will transfer from Co to Pt, causing the d-band center of Pt to shift downward. After the d-band center shifts downward, the adsorption strength of oxygen-containing intermediate species of Pt is weakened, thereby reducing the energy barrier for the breaking of OO bonds in the oxygen reduction reaction and thus improving the intrinsic catalytic activity.
[0024] 10. In this invention, at the working potential of a fuel cell, the surface atoms of pure Pt are easily oxidized and dissolved, and the Co atoms in the alloy are thermodynamically more easily oxidized. Therefore, Co protects the Pt atoms and changes the oxidation potential of the Pt surface, thereby significantly improving the electrochemical stability of Pt. The ordered Pt3Co structure has higher formation energy and thermal stability, which can effectively suppress the Ostwald ripening process of small particle dissolution and large particle growth. Attached Figure Description
[0025] Figure 1 This is a flowchart of a high-performance proton exchange membrane fuel cell catalyst material and its preparation method proposed in this invention. Detailed Implementation
[0026] The technical solutions of the present invention will be clearly and completely described below with reference to the accompanying drawings of the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention.
[0027] It should be noted that, in this document, relational terms such as "first" and "second" are used only to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such a process, method, article, or apparatus. Without further limitation, an element defined by the phrase "comprising..." does not exclude the presence of other identical elements in the process, method, article, or apparatus that includes said element.
[0028] Example 1 This embodiment provides a high-performance proton exchange membrane fuel cell catalyst material and its preparation method, the specific implementation steps of which include: Experimental materials: The following are the ingredients: graphene oxide dispersion with a C / O ratio of 4.0, ascorbic acid, 0.1 mol / L cobalt nitrate aqueous solution, 0.8 mol / L 2-methylimidazole, 5 mg / mL chloroplatinic acid ethanol solution, anhydrous lithium chloride, anhydrous potassium chloride, methanol, and deionized water.
[0029] Experimental objective: The proton exchange membrane fuel cell catalyst was developed by constructing a three-dimensional graphene confined support and using a low-temperature molten salt method to achieve the ordered formation of Pt3Co intermetallic compounds at 500℃.
[0030] Experimental steps: S1: Take 100 mL of graphene oxide dispersion with a concentration of 2 mg / mL into a 200 mL polytetrafluoroethylene inner vessel, then add 0.5 g ascorbic acid as a reducing agent and stir magnetically for 30 minutes to mix it evenly. Place the inner vessel into the reaction vessel and react it at 95℃ for 6 hours. Finally, cool it to room temperature and wash the gel with deionized water. S2: Add 100 mL of 0.1 mol / L cobalt nitrate aqueous solution to the gel prepared in S1, then let it stand for 12 hours to adsorb, and finally rinse the surface with deionized water to remove excess salt solution after adsorption. S3: Take 50 mL of 0.8 mol / L 2-methylimidazolium methanol solution and add the gel prepared in S2 to it. Then let it stand at room temperature of 25°C for 6 hours. After the reaction is completed, wash the gel with methanol. S4: The gel prepared in S3 was freeze-dried for 24 hours, then the gel was ball-milled into powder, and then the powder was placed in a tube furnace under an argon atmosphere and heated to 350°C at a rate of 2°C / min and held for 1 hour. Then the temperature was increased to 900°C at a rate of 5°C / min and held for 2 hours to obtain a three-dimensional graphene / cobalt nitrogen carbon microcage composite carrier. S5: Weigh 60 mL of the prepared chloroplatinic acid ethanol solution with a concentration of 5 mg / mL, then weigh 0.2 g of the three-dimensional graphene / cobalt nitrogen carbon microcage composite carrier obtained in S4, add the chloroplatinic acid ethanol solution dropwise while stirring into the three-dimensional graphene / cobalt nitrogen carbon microcage composite carrier, age it at 25°C for 6 hours, and finally dry it in a 60°C oven for 12 hours to obtain the precursor. S6: Anhydrous LiCl and KCl were mixed in a mass ratio of 45:55 and ball-milled uniformly. Then, the precursor powder prepared in S4 was ball-milled with the mixed powder of LiCl and KCl at a mass ratio of 1:8 for 30 minutes. The ground powder was then placed in a tube furnace under a 10% H2 / Ar mixed atmosphere and heated to 500℃ at a rate of 5℃ / min and held for 3 hours. After the product cooled to room temperature, it was washed with 80℃ hot water until no chloride ions were detected. Then, it was kept in 1M nitric acid at 90℃ for 2 hours and washed clean with deionized water. Finally, the product was dried in an 80℃ vacuum oven for 12 hours to obtain Pt3Co / G@CoNC. S7: Weigh 80 mg of Pt3Co / G@CoNC prepared in S6 and 20 mg of ionomer D79, then add 5 mL of deionized water and 12 mL of isopropanol. Disperse the mixture ultrasonically in an ice-water bath for 1 hour to obtain a cathode catalyst slurry. Spray the cathode catalyst slurry onto one side of a 5 cm × 5 cm proton exchange membrane, controlling the cathode platinum loading at 0.15–0.20 mg Pt / cm². 2 The anode slurry uses a Pt / C catalyst with a Pt / C ratio of 20% and is sprayed onto the other side of the proton exchange membrane to control the platinum loading of the anode at 0.05~0.10 mg Pt / cm³. 2 Finally, after the coating is completed, the film is dried at 60°C for 2 hours, and the frame and diffusion layer are bonded together to form a film electrode. S8: Assemble the prepared membrane electrode into a single cell, then connect it to the gas pipeline and circuit. Control the cell to be energized by gas and constant current under the conditions of 80°C, 100% relative humidity, and 150kPa (abs) back pressure. Obtain the voltage at different current densities. Apply a square wave voltage alternately at 0.6V and 0.95V every 3 seconds to perform 30,000 accelerated durability tests.
[0031] Experimental results: See Table 1 for details.
[0032] Table 1: Test Results of Example 1
[0033] Example 1 synthesized a high-performance proton exchange membrane fuel cell catalyst material. This material, based on a three-dimensional graphene framework as a conductive network, formed a continuous porous structure through hydrothermal reduction self-assembly at 95°C, significantly improving the overall conductivity and structural stability of the material. Based on this, a 0.1 mol / L cobalt nitrate aqueous solution was used to react with Co... 2+ Adsorption and in-situ growth of ZIF-67 crystals in combination with 2-methylimidazole solution, followed by two-step pyrolysis to transform into crystals rich in Co-N x Cobalt-nitrogen-carbon microcages with active sites effectively combine high specific surface area with active sites. Subsequently, ordered Pt3Co alloy nanoparticles were synthesized on a composite support via a low-temperature molten salt method. This structure effectively inhibits particle aggregation and growth while enhancing catalytic activity. The catalyst exhibited excellent polarization performance (0.2 A / cm²) in fuel cell testing. 2 Voltage up to 0.78V, 1.0A / cm 2 The voltage is 0.68V, and the peak power density reaches 1.25W / cm². 2 Furthermore, after 30,000 accelerated durability tests, the power retention rate was 85%.
[0034] Example 2 This embodiment provides a high-performance proton exchange membrane fuel cell catalyst material and its preparation method, the specific implementation steps of which include: Experimental materials: The following are the ingredients: graphene oxide dispersion with a C / O ratio of 4.0, ascorbic acid, 0.1 mol / L cobalt nitrate aqueous solution, 0.8 mol / L 2-methylimidazole, 5 mg / mL chloroplatinic acid ethanol solution, anhydrous lithium chloride, anhydrous potassium chloride, methanol, and deionized water.
[0035] Experimental objective: To investigate the effect of reduction temperature on catalyst performance.
[0036] Experimental steps: S1: Take 100 mL of graphene oxide dispersion with a concentration of 2 mg / mL into a 200 mL polytetrafluoroethylene inner vessel, then add 0.5 g ascorbic acid as a reducing agent and stir magnetically for 30 minutes to mix it evenly. Place the inner vessel into the reaction vessel and place it at 70℃ for 6 hours. Finally, cool to room temperature and wash the gel with deionized water. S2: Add 100 mL of 0.1 mol / L cobalt nitrate aqueous solution to the gel prepared in S1, then let it stand for 12 hours to adsorb, and finally rinse the surface with deionized water to remove excess salt solution after adsorption. S3: Take 50 mL of 0.8 mol / L 2-methylimidazolium methanol solution and add the gel prepared in S2 to it. Then let it stand at room temperature of 25°C for 6 hours. After the reaction is completed, wash the gel with methanol. S4: Freeze-dry the gel prepared in S3 for 24 hours, then ball-mill the gel into powder, then place the powder in a tube furnace under an argon atmosphere and heat it to 350°C at a rate of 2°C / min and hold it for 1 hour, then heat it to 900°C at a rate of 5°C / min and hold it for 2 hours to obtain a three-dimensional graphene / cobalt nitrogen carbon microcage composite carrier. S5: Weigh 60 mL of the prepared chloroplatinic acid ethanol solution with a concentration of 5 mg / mL, then weigh 0.2 g of the three-dimensional graphene / cobalt nitrogen carbon microcage composite carrier obtained in S4, add the chloroplatinic acid ethanol solution dropwise while stirring into the three-dimensional graphene / cobalt nitrogen carbon microcage composite carrier, age it at 25°C for 6 hours, and finally dry it in a 60°C oven for 12 hours to obtain the precursor. S6: Anhydrous LiCl and KCl were mixed in a mass ratio of 45:55 and ball-milled into powder. Then, the precursor powder prepared in S4 was ball-milled with the mixed powder of LiCl and KCl at a mass ratio of 1:8 for 30 minutes. The ball-milled powder was then placed in a tube furnace under a 10% H2 / Ar mixed atmosphere and heated to 500℃ at a rate of 5℃ / min and held for 3 hours. After the product cooled to room temperature, it was washed with 80℃ hot water until no chloride ions were detected. Then, it was kept in 1M nitric acid at 90℃ for 2 hours and washed with deionized water. Finally, the product was dried in an 80℃ vacuum oven for 12 hours to obtain Pt3Co / G@CoNC. S7: Weigh 80 mg of Pt3Co / G@CoNC prepared in S6 and 20 mg of ionomer D79, then add 5 mL of deionized water and 12 mL of isopropanol. Disperse the mixture ultrasonically in an ice-water bath for 1 hour to obtain a cathode catalyst slurry. Spray the cathode catalyst slurry onto one side of a 5 cm × 5 cm proton exchange membrane, controlling the cathode platinum loading to be 0.15–0.20 mg Pt / cm². 2 The anode slurry uses a Pt / C catalyst with a Pt / C ratio of 20% and is sprayed onto the other side of the proton exchange membrane to control the platinum loading of the anode at 0.05~0.10 mg Pt / cm³. 2 Finally, after the coating is completed, the film is dried at 60°C for 2 hours, and the frame and diffusion layer are bonded together to form a film electrode. S8: Assemble the prepared membrane electrode into a single cell, connect the gas pipeline and the circuit, control the cell to be activated by constant current by randomly introducing gas at a cell temperature of 80°C, relative humidity of 100%, and back pressure of 150 kPa (abs), and obtain the voltage at different current densities; and perform 30,000 accelerated durability tests by alternately applying a square wave voltage of 0.6V and 0.95V every 3 seconds.
[0037] Experimental results: See Table 2 for details.
[0038] Table 2: Test Results of Example 2
[0039] In Example 2, the reduction temperature was lowered to 70°C, resulting in insufficient reduction of graphene oxide and the depletion of graphene conjugated sp. 2 Insufficient structure formation and a loose three-dimensional network structure; at the same time, an increase in unreduced oxygen-containing groups affects Co. 2+ The coordination adsorption and subsequent ZIF-67 crystal growth ultimately led to an uneven distribution of active sites on the support, resulting in a comprehensive decline in catalytic performance. Structural defects in the support caused an uneven distribution of active sites in the cobalt-nitrogen-carbon microcage, ultimately leading to a significant decrease in its polarization performance (0.2 A / cm). 2The voltage is 0.70V, and the current is 1.0A / cm. 2 With the voltage reduced to 0.58V, the peak power density is only 0.82W / cm². 2 Furthermore, the power retention rate after 30,000 AST cycles was only 62%, indicating that the reduction temperature has a significant impact on the overall performance of the catalyst.
[0040] Example 3 This embodiment provides a high-performance proton exchange membrane fuel cell catalyst material and its preparation method, the specific implementation steps of which include: Experimental materials: The following are the ingredients: graphene oxide dispersion with a C / O ratio of 4.0, ascorbic acid, 0.05 mol / L cobalt nitrate aqueous solution, 0.8 mol / L 2-methylimidazole, 5 mg / mL chloroplatinic acid ethanol solution, anhydrous lithium chloride, anhydrous potassium chloride, methanol, and deionized water.
[0041] Experimental objective: Investigate the effect of Co loading concentration on performance.
[0042] Experimental steps: S1: Take 100 mL of graphene oxide dispersion with a concentration of 2 mg / mL into a 200 mL polytetrafluoroethylene inner vessel, then add 0.5 g ascorbic acid as a reducing agent and stir magnetically for 30 minutes to mix it evenly. Place the inner vessel into the reaction vessel and react it at 95℃ for 6 hours. Finally, cool it to room temperature and wash the gel with deionized water. S2: Add 100 mL of 0.05 mol / L cobalt nitrate aqueous solution to the gel prepared in S1, then let it stand for 12 hours to adsorb, and finally rinse the surface with deionized water to remove excess salt solution after adsorption. S3: Take 50 mL of 0.8 mol / L 2-methylimidazolium methanol solution and add the gel prepared in S2 to it. Then let it stand at room temperature of 25°C for 6 hours. After the reaction is completed, wash the gel with methanol. S4: The gel prepared in S3 was freeze-dried for 24 hours, then the gel was ball-milled into powder, and then the powder was placed in a tube furnace under an argon atmosphere and heated to 350°C at a rate of 2°C / min and held for 1 hour. Then the temperature was increased to 900°C at a rate of 5°C / min and held for 2 hours to obtain a three-dimensional graphene / cobalt nitrogen carbon microcage composite carrier. S5: Weigh 60 mL of the prepared chloroplatinic acid ethanol solution with a concentration of 5 mg / mL, then weigh 0.2 g of the three-dimensional graphene / cobalt nitrogen carbon microcage composite carrier obtained in S4, add the chloroplatinic acid ethanol solution dropwise while stirring into the three-dimensional graphene / cobalt nitrogen carbon microcage composite carrier, age it at 25°C for 6 hours, and finally dry it in a 60°C oven for 12 hours to obtain the precursor. S6: Anhydrous LiCl and KCl were mixed in a mass ratio of 45:55 and ball-milled. Then, the precursor powder prepared in S4 was ball-milled with the mixed powder of LiCl and KCl at a mass ratio of 1:8 for 30 minutes. The ball-milled powder was then placed in a tube furnace under a 10% H2 / Ar mixed atmosphere and heated to 500℃ at a rate of 5℃ / min and held for 3 hours. After the product cooled to room temperature, it was washed with 80℃ hot water until no chloride ions were detected. Then, it was kept in 1M nitric acid at 90℃ for 2 hours and washed clean with deionized water. Finally, the product was dried in an 80℃ vacuum oven for 12 hours to obtain Pt3Co / G@CoNC. S7: Weigh 80 mg of Pt3Co / G@CoNC prepared in S6 and 20 mg of ionomer D79, then add 5 mL of deionized water and 12 mL of isopropanol. Disperse the mixture ultrasonically in an ice-water bath for 1 hour to obtain a cathode catalyst slurry. Spray the cathode catalyst slurry onto one side of a 5 cm × 5 cm proton exchange membrane, controlling the cathode platinum loading to be 0.15–0.20 mg Pt / cm². 2 The anode slurry uses a Pt / C catalyst with a Pt / C ratio of 20% and is sprayed onto the other side of the proton exchange membrane to control the platinum loading of the anode at 0.05~0.10 mg Pt / cm³. 2 Finally, after the coating is completed, place the film in an environment of 60℃ to dry for 2 hours; S8: Assemble the prepared membrane electrode with the gas diffusion layer and flow field plate into a single cell, then connect the gas pipeline and circuit, and control the cell to be activated by constant current by passing gas through it under the conditions of 80°C cell temperature, 100% relative humidity and 150kPa (abs) back pressure, and obtain the voltage under different current densities; and perform 30,000 accelerated durability tests by alternating voltage square wave cycles of 0.6V and 0.95V every 3 seconds.
[0043] Experimental results: See Table 3 for details.
[0044] Table 3: Test Results of Example 3
[0045] In Example 3, Co 2+ The reduced concentration decreases the number of Co sites adsorbed on the graphene framework, thus limiting the growth of ZIF-67 crystals, resulting in insufficient number of derived CoNC microcages and reduced Co-N active sites. x The density decreases; simultaneously, insufficient Co atom supply during Pt3Co alloying affects the degree of ordered alloy formation, thereby reducing catalytic activity and stability. This structural defect leads to a decrease in catalytic performance: 0.2 A / cm³. 2 The voltage is 0.74V, and the current is 1.0A / cm. 2The voltage is 0.62V, and the peak power density is 0.98W / cm². 2 The power retention rate was 72% after 30,000 AST cycles, indicating that the Co loading plays an important role in regulating the activity and stability of the catalyst.
[0046] Example 4 This embodiment provides a high-performance proton exchange membrane fuel cell catalyst material and its preparation method, the specific implementation steps of which include: Experimental materials: The following are the ingredients: graphene oxide dispersion with a C / O ratio of 4.0, ascorbic acid, 0.1 mol / L cobalt nitrate aqueous solution, 0.8 mol / L 2-methylimidazole, 5 mg / mL chloroplatinic acid ethanol solution, anhydrous lithium chloride, anhydrous potassium chloride, methanol, and deionized water.
[0047] Experimental objective: To investigate the effect of molten salt ratio on the degree of ordering in alloys.
[0048] Experimental steps: S1: Take 100 mL of graphene oxide dispersion with a concentration of 2 mg / mL into a 200 mL polytetrafluoroethylene inner vessel, then add 0.5 g ascorbic acid as a reducing agent and stir magnetically for 30 minutes to mix it evenly. Place the inner vessel into the reaction vessel and react it at 95℃ for 6 hours. Finally, cool it to room temperature and wash the gel with deionized water. S2: Add 100 mL of 0.1 mol / L cobalt nitrate aqueous solution to the gel prepared in S1, then let it stand for 12 hours to adsorb, and finally rinse the surface with deionized water to remove excess salt solution after adsorption. S3: Take 50 mL of 0.8 mol / L 2-methylimidazolium methanol solution and add the gel prepared in S2 to it. Then let it stand at room temperature of 25°C for 6 hours. After the reaction is completed, wash the gel with methanol. S4: The gel prepared in S3 was freeze-dried for 24 hours, then the gel was ball-milled into powder, and then the powder was placed in a tube furnace under an argon atmosphere and heated to 350°C at a rate of 2°C / min and held for 1 hour. Then the temperature was increased to 900°C at a rate of 5°C / min and held for 2 hours to obtain a three-dimensional graphene / cobalt nitrogen carbon microcage composite carrier. S5: Weigh 60 mL of the prepared chloroplatinic acid ethanol solution with a concentration of 5 mg / mL, then weigh 0.2 g of the three-dimensional graphene / cobalt nitrogen carbon microcage composite carrier obtained in S4, add the chloroplatinic acid ethanol solution dropwise while stirring into the three-dimensional graphene / cobalt nitrogen carbon microcage composite carrier, age it at 25°C for 6 hours, and finally dry it in a 60°C oven for 12 hours to obtain the precursor. S6: Anhydrous LiCl and KCl were mixed in a mass ratio of 30:70 and ball-milled into powder. Then, the precursor powder prepared in S4 was ball-milled with the mixed powder of LiCl and KCl at a mass ratio of 1:8 for 30 minutes. The ball-milled powder was then placed in a tube furnace under a 10% H2 / Ar mixed atmosphere and heated to 500℃ at a rate of 5℃ / min and held for 3 hours. After the product cooled to room temperature, it was washed with 80℃ hot water until no chloride ions were detected. Then, it was kept in 1M nitric acid at 90℃ for 2 hours and washed with deionized water. Finally, the product was dried in an 80℃ vacuum oven for 12 hours to obtain Pt3Co / G@CoNC. S7: Weigh 80 mg of Pt3Co / G@CoNC prepared in S6 and 20 mg of ionomer D79, then add 5 mL of deionized water and 12 mL of isopropanol. Disperse the mixture ultrasonically in an ice-water bath for 1 hour to obtain a cathode catalyst slurry. Spray the cathode catalyst slurry onto one side of a 5 cm × 5 cm proton exchange membrane, controlling the cathode platinum loading to be 0.15–0.20 mg Pt / cm². 2 The anode slurry uses a Pt / C catalyst with a Pt / C ratio of 20% and is sprayed onto the other side of the proton exchange membrane to control the platinum loading of the anode at 0.05~0.10 mg Pt / cm³. 2 Finally, after the coating is completed, place the film in an environment of 60℃ to dry for 2 hours; S8: Assemble the prepared membrane electrode with the gas diffusion layer and flow field plate into a single cell, then connect the gas pipeline and circuit, and control the cell to be activated by constant current by passing gas through it under the conditions of 80°C cell temperature, 100% relative humidity and 150kPa (abs) back pressure, and obtain the voltage under different current densities; and perform 30,000 accelerated durability tests by alternating voltage square wave cycles of 0.6V and 0.95V every 3 seconds.
[0049] Experimental results: See Table 4 for details.
[0050] Table 4: Test Results of Example 4
[0051] With a LiCl:KCl mass ratio of 30:70, the fluidity, wettability, and ionic interactions between the molten salt and Pt / Co are weakened, leading to an increase in the atomic diffusion barrier and a decrease in orderliness during alloying. Simultaneously, the micropore confinement effect is weakened, reducing the ability to control particle size, ultimately affecting the electrochemical activity and durability of the catalyst. The resulting catalyst maintains a certain level of activity and polarization performance at 0.2 A / cm². 2 Voltage 0.76V, 1.0A / cm 2 Voltage 0.64V, peak power density 1.08W / cm³ 2The power retention rate was 78% after 30,000 AST cycles, indicating that the molten salt ratio has a key impact on the degree of alloy ordering and long-term durability.
[0052] Example 5 This embodiment provides a high-performance proton exchange membrane fuel cell catalyst material and its preparation method, the specific implementation steps of which include: Experimental materials: The following ingredients were present: graphene oxide dispersion with a C / O ratio of 4.0, ascorbic acid, 0.1 mol / L cobalt nitrate aqueous solution, 5 mg / mL chloroplatinic acid ethanol solution, anhydrous lithium chloride, anhydrous potassium chloride, methanol, and deionized water.
[0053] Experimental objective: To investigate the effect of ZIF-67 crystal absence on the structure and properties of the carrier.
[0054] Experimental steps: S1: Take 100 mL of graphene oxide dispersion with a concentration of 2 mg / mL into a 200 mL polytetrafluoroethylene inner vessel, then add 0.5 g ascorbic acid as a reducing agent and stir magnetically for 30 minutes to mix it evenly. Place the inner vessel into the reaction vessel and react it at 95℃ for 6 hours. Finally, cool it to room temperature and wash the gel with deionized water. S2: Add 100 mL of 0.1 mol / L cobalt nitrate aqueous solution to the gel prepared in S1, then let it stand for 12 hours to adsorb, and finally rinse the surface with deionized water to remove excess salt solution after adsorption. S3: Freeze-dry the gel prepared in S2 for 24 hours, then ball-mill the gel into powder, then place the powder in a tube furnace under an argon atmosphere and heat it to 350°C at a rate of 2°C / min and hold it for 1 hour, then heat it to 900°C at a rate of 5°C / min and hold it for 2 hours to obtain the composite carrier. S4: Weigh 60 mL of the prepared chloroplatinic acid ethanol solution with a concentration of 5 mg / mL, then weigh 0.2 g of the composite carrier obtained in S4, add the chloroplatinic acid ethanol solution dropwise while stirring, then age it at 25°C for 6 hours, and finally dry it in a 60°C oven for 12 hours to obtain the precursor. S5: Anhydrous LiCl and KCl were mixed in a mass ratio of 45:55 and ball-milled into powder. Then, the precursor powder prepared in S4 was ball-milled with the mixed powder of LiCl and KCl at a mass ratio of 1:8 for 30 minutes. The ball-milled powder was then placed in a tube furnace under a 10% H2 / Ar mixed atmosphere and heated to 500℃ at a rate of 5℃ / min and held for 3 hours. After the product cooled to room temperature, it was washed with 80℃ hot water until no chloride ions were detected. Then, it was kept in 1M nitric acid at 90℃ for 2 hours and washed with deionized water. Finally, the product was dried in an 80℃ vacuum oven for 12 hours to obtain the graphene / cobalt composite support. S7: Weigh 80 mg of Pt3Co / G@CoNC prepared in S6 and 20 mg of ionomer D79, then add 5 mL of deionized water and 12 mL of isopropanol. Disperse the mixture ultrasonically in an ice-water bath for 1 hour to obtain a cathode catalyst slurry. Spray the cathode catalyst slurry onto one side of a 5 cm × 5 cm proton exchange membrane, controlling the cathode platinum loading at 0.15–0.20 mg Pt / cm². 2 The anode slurry uses a Pt / C catalyst with a Pt / C ratio of 20% and is sprayed onto the other side of the proton exchange membrane to control the platinum loading of the anode at 0.05~0.10 mg Pt / cm³. 2 Finally, after the coating is completed, the film is dried at 60°C for 2 hours, and the frame and diffusion layer are bonded together to form a film electrode. S8: The prepared membrane electrode is assembled into a single cell, and then connected to the gas pipeline and circuit. The cell is activated by gas being introduced at a constant current mode under the control of a cell temperature of 80°C, relative humidity of 100%, and back pressure of 150 kPa (abs). The voltage at different current densities is obtained. A square wave voltage of 0.6V and 0.95V is applied alternately every 3 seconds to perform 30,000 accelerated durability tests.
[0055] Experimental results: See Table 5 for details.
[0056] Table 5: Test Results of Example 5
[0057] Example 5 skips the ZIF-67 crystal growth step; the support is only a simple graphene / Co composite, lacking porosity and rich in Co-N. x The carbon cage structure of the sites leads to a significant reduction in specific surface area and a lack of active sites; the Pt-supported catalyst exhibits poor dispersibility and cannot form an effective confinement effect, resulting in easy particle agglomeration during alloying and a substantial decrease in catalytic performance. The performance of the resulting catalyst deteriorates significantly by 0.2 A / cm². 2 The voltage is only 0.65V, 1.0A / cm. 2With the voltage reduced to 0.50V, the peak power density is only 0.65W / cm². 2 The power retention rate was as low as 48% after 30,000 AST cycles, indicating that ZIF-67-derived cobalt-nitrogen-carbon microcages play an irreplaceable role in constructing highly active and stable supports.
[0058] Comparative Example 1 This embodiment provides a method for preparing a conventional Pt / C fuel cell catalyst, and the specific implementation steps include: Experimental materials: Carbon black, chloroplatinic acid, deionized water, isopropanol, solution, hydrogen, argon.
[0059] Experimental objective: Preparation of traditional Pt / C carbon-supported platinum catalysts.
[0060] Experimental steps: S1: Disperse 0.6 g of carbon black in 100 mL of ethanol and sonicate at a frequency of 50 kHz for 1 hour; S2: Weigh 1g of chloroplatinic acid, dissolve it in 10mL of deionized water, add the pretreated carbon black as described above, and stir at 200rpm for 1 hour at room temperature. Then place it in a 60℃ oven to dry for 12 hours. S3: The above premixture was then placed in a tube furnace under a hydrogen / argon atmosphere and heated to 300°C at 5°C / min and held for 2 hours. The product was then cooled to room temperature. S4: Wash the cooled product of S3 with deionized water and dry it in a vacuum drying oven at 80°C for 12 hours to obtain a 38wt.% Pt / C catalyst; S5: 80 mg Pt / C catalyst, 20 mg ionomer D79, 5 mL deionized water, and 12 mL isopropanol were mixed and ultrasonically dispersed in an ice-water bath for 1 hour to obtain a cathode catalyst slurry. This slurry was then sprayed onto one side of a 5 cm × 5 cm membrane, with the platinum loading controlled at 0.17 mg Pt / cm². 2 ; S6: Use 20wt% Pt / C catalyst at the anode, controlling the loading to 0.06mg Pt / cm. 2 Then, single cells were assembled and their performance was tested under conditions of 80°C, 100% humidity, and 150 kPa.
[0061] Experimental results: See Table 6 for details.
[0062] Table 6: Test Results of Comparative Example 1
[0063] Traditional Pt / C catalysts, supported by ordinary carbon black, lack a three-dimensional conductive network and porous confined structure, resulting in uneven platinum particle dispersion, easy agglomeration, and the absence of Co-N. x The presence of synergistic active sites results in a small electrochemical active area, low catalytic efficiency, and poor stability. Its performance deteriorates significantly in accelerated stress testing, and its overall performance is far inferior to the catalyst proposed in this invention, with a polarization performance of 0.2 A / cm. 2 Voltage 0.68V, 1.0A / cm 2 With a voltage of 0.55V, the peak power density is only 0.70W / cm³. 2 Furthermore, the power retention rate after 30,000 AST cycles is only 45%, and the overall performance is significantly inferior to the catalyst system proposed in this invention.
[0064] Example 1 employs a triple synergistic strategy of three-dimensional graphene confinement support, ZIF-67-derived cobalt-nitrogen-carbon microcages, and low-temperature molten salt ordered alloying, achieving hydrothermal reduction at 95℃ and 0.1 mol / L Co. 2+ Adsorption, in-situ growth of ZIF-67 crystals, two-step pyrolysis, and low-temperature molten salt conditions of LiCl:KCl=45:55 were used to construct a highly conductive network, a porous confined structure, and abundant Co-N. x The Pt3Co ordered alloy catalyst with active sites exhibits excellent electrochemical active area, low Tafel slope, high current density and good long-term stability.
[0065] Example 2 used a lower reduction temperature for hydrothermal reduction, resulting in insufficient reduction of graphene oxide and a loose three-dimensional graphene framework structure. 2+ Adsorption and ZIF-67 crystal growth are limited, and the distribution of active sites on the support is uneven, ultimately leading to a comprehensive decline in catalyst performance.
[0066] Example 3 uses a lower Co 2+ Concentration leads to insufficient Co sites on the graphene framework, limiting the growth of ZIF-67 crystals, reducing the number of derived CoNC microcages, and affecting Co-N concentration. x The reduced density of active sites, coupled with insufficient Co atom supply during Pt3Co alloying, affected the degree of ordered alloy formation, resulting in a decrease in both catalytic activity and stability.
[0067] Example 4 uses an unconventional molten salt ratio, which weakens the fluidity and wettability of the molten salt and the interaction between ions and Pt / Co, increases the atomic diffusion barrier, decreases the degree of order, weakens the micropore confinement effect, and reduces the ability to control particle size, thereby affecting the electrochemical activity and durability of the catalyst.
[0068] Example 5 skips the ZIF-67 crystal growth step and only uses Co... 2+The graphene / cobalt composite support is obtained by direct pyrolysis after adsorption, which is poorly porous and rich in Co-N. x The carbon cage structure of the sites leads to a significant reduction in specific surface area and a lack of active sites. After Pt loading, the dispersion is poor, and an effective confinement effect cannot be formed. During the alloying process, the particles are prone to agglomeration, resulting in a significant decrease in catalytic performance.
[0069] Comparative Example 1 illustrates a traditional Pt / C catalyst preparation method. Using carbon black as a support, a 20 wt.% Pt / C catalyst was prepared via an impregnation-reduction method. However, this method suffers from drawbacks due to the lack of a three-dimensional conductive network, porous confined structure, and Co-N composite material on the support. x Due to the presence of synergistic active sites, Pt particles are unevenly dispersed, prone to migration and aggregation, and have limited electron conduction and mass transfer capabilities. Furthermore, the lack of a low-temperature ordered alloying strategy during the preparation process results in poor catalyst stability at high potentials and overall inferior performance.
[0070] This invention utilizes a triple synergistic strategy of a three-dimensional graphene framework, ZIF-67-derived cobalt-nitrogen-carbon microcages, and low-temperature molten salt ordered alloying to prepare a highly conductive network, a porous confined structure, and abundant Co-N. x The Pt3Co ordered alloy catalyst with active sites retains ≥80% of its activity after 30,000 AST cycles; Examples 2 to 5 show that hydrothermal temperature and Co 2+ Deviations in concentration, molten salt ratio, and ZIF-67 growth steps can all lead to structural defects in the support, a reduction in active sites, or a decrease in alloy order, resulting in varying degrees of performance degradation. In contrast, the traditional Pt / C catalyst in Comparative Example 1, lacking the aforementioned synergistic structure and ordered alloying strategy, exhibits significantly inferior performance, highlighting the remarkable advantages of this invention in improving catalyst activity, stability, and reducing platinum loading.
[0071] The above description is merely a specific embodiment of this application, but the scope of protection of this application is not limited thereto. Any variations or substitutions that can be easily conceived by those skilled in the art within the scope of the technology disclosed in this application should be included within the scope of protection of this application. Therefore, the scope of protection of this application should be determined by the scope of protection of the claims.
[0072] In conclusion, the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A method for preparing a high-performance proton exchange membrane fuel cell catalyst material, characterized in that, Specifically, it is composed of a three-dimensional graphene framework, cobalt-nitrogen-carbon microcages, and ordered Pt3Co alloy nanoparticles; the three-dimensional graphene framework is a continuous porous three-dimensional network structure formed by hydrothermal reduction self-assembly; the cobalt-nitrogen-carbon microcages are porous carbon cage structures with Co-N x Active sites are embedded in Co nanoparticles; the ordered Pt3Co alloy nanoparticles are ordered intermetallic compounds; cobalt-nitrogen-carbon microcages are tightly embedded in the nodes of the three-dimensional graphene network, and the ordered Pt3Co alloy nanoparticles are distributed in the pores of the cobalt-nitrogen-carbon microcages. Includes the following steps: S1: Take 100 parts by volume of graphene oxide dispersion with a concentration of 2 mg / mL into a polytetrafluoroethylene inner vessel, then add 0.5 parts by weight of ascorbic acid as a reducing agent and stir magnetically for 30 minutes to mix it evenly. Place the inner vessel into the reaction vessel and heat it to 70~100℃ and keep it at that temperature for 6~12 hours. Finally, cool it to room temperature and wash the gel with deionized water. S2: Add 100 volumes of cobalt nitrate aqueous solution to the gel prepared in S1, then let it stand for 12 hours to adsorb, and finally rinse the surface with deionized water to remove excess salt solution after adsorption. S3: Take 50 volume parts of 0.8 mol / L 2-methylimidazolium methanol solution and add it to the gel prepared in S2. Then let it stand at room temperature of 25°C for 6 hours. After the reaction is completed, wash the gel with methanol. S4: The gel prepared in S3 was freeze-dried for 24 hours, then the gel was ground into powder, and then the powder was placed in a tube furnace under an argon atmosphere and heated stepwise to obtain a three-dimensional graphene / cobalt nitrogen carbon microcage composite carrier. S5: Weigh 60 volume parts of the prepared chloroplatinic acid ethanol solution with a concentration of 5 mg / mL, then weigh 0.5 weight parts of the three-dimensional graphene / cobalt nitrogen carbon microcage composite support obtained in S4, add the chloroplatinic acid ethanol solution dropwise and stir into the three-dimensional graphene / cobalt nitrogen carbon microcage composite support, then age it at 25°C for 6 hours, and finally dry it in a 60°C oven for 12 hours to obtain the catalyst precursor. S6: Anhydrous LiCl and KCl were uniformly ground into powder. Then, the catalyst precursor powder prepared in S5 was ball-milled with the mixed powder of LiCl and KCl for 30 minutes. The ground powder was then placed in a tube furnace under a 10% H2 / Ar mixed atmosphere and heated to 500℃ at a rate of 5℃ / min and held for 3 hours. After the product cooled to room temperature, it was washed with 80℃ hot water until no chloride ions were detected. Then, it was kept in 1M nitric acid at 90℃ for 2 hours and washed clean with deionized water. Finally, the product was dried in an 80℃ vacuum oven for 12 hours to obtain Pt3Co / G@CoNC.
2. The method for preparing a high-performance proton exchange membrane fuel cell catalyst material as described in claim 1, characterized in that, The concentration of cobalt nitrate aqueous solution in S2 is 0.05~0.15 mol / L.
3. The method for preparing a high-performance proton exchange membrane fuel cell catalyst material as described in claim 1, characterized in that, In S4, the ground powder is placed in a tube furnace under an argon atmosphere and heated to 350°C at a heating rate of 2°C / min and held for 1 hour. Then, it is heated to 900°C at a heating rate of 5°C / min and held for 2 hours.
4. The method for preparing a high-performance proton exchange membrane fuel cell catalyst material as described in claim 1, characterized in that, The mass ratio of LiCl to KCl in S6 is 25~50:50~75.
Citation Information
Patent Citations
Method for synthesizing a small-size high-dispersion intermetallic compound catalyst material and application
CN110649273A